The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.32502/jimn.v8i1.1557
|View full text |Cite
|
Sign up to set email alerts
|

Perbandingan Keakuratan Capital Assets Pricing Model (Capm) Dan Arbitrage Pricing Theory (Apt) Dalam Menentukan Pilihan Berinvestasi Pada Saham Jakarta Islamic Index (Jii)

Abstract: The formulation of the problem in this study was how the accuracy of the Capital Asset Pricing Model (CAPM) and Arbitrage Pricing Theory (APT) in Determining the Choice of Investing in the Jakarta Islamic Index (JII). The objective of this study was to find out the differences of the Capital Asset Pricing Model (CAPM) and Arbitrage Pricing Theory (APT) in Determining the Choice of Investing in the Jakarta Islamic Index (JII). There were two balance methods that are still used as the approach material for accur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
0
2
0
5
Order By: Relevance
“…There have been several previous studies that discuss the accuracy of the balance model in determining investment, namely research conducted by (Östermark, 1990) (Juwana, 2015), (Laila & Saerang, 2015), and (Pham, 2020) with results indicating that APT is a more accurate model used in the calculation of the expected return of shares compared to CAPM. While according to (Lemiyana, 2015), (Indra, 2018), (Safitri et al, 2018), and (Muhammad, 2019) with the results of the study showed that the CAPM model is more accurate in predicting stock return when compared to APT. This study seeks to analyze which balance model is more accurate in predicting stock investments and determine the differences in the accuracy of the Capital Asset Pricing Model (CPAM) and Arbitrage Pricing Theory (APT) models in determining investment options.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…There have been several previous studies that discuss the accuracy of the balance model in determining investment, namely research conducted by (Östermark, 1990) (Juwana, 2015), (Laila & Saerang, 2015), and (Pham, 2020) with results indicating that APT is a more accurate model used in the calculation of the expected return of shares compared to CAPM. While according to (Lemiyana, 2015), (Indra, 2018), (Safitri et al, 2018), and (Muhammad, 2019) with the results of the study showed that the CAPM model is more accurate in predicting stock return when compared to APT. This study seeks to analyze which balance model is more accurate in predicting stock investments and determine the differences in the accuracy of the Capital Asset Pricing Model (CPAM) and Arbitrage Pricing Theory (APT) models in determining investment options.…”
Section: Introductionmentioning
confidence: 81%
“…The preparation of this portfolio can be done with two models often used by investors, namely Capital Asset Pricing Model (CAPM) and Arbitrage Pricing Model (APT). Financial management experts still debate both models' accuracy in predicting risks and returns (Safitri et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Kemudian penelitian Gulam, (2019) pada hasil perhitungan metode CAPM lebih tepat atau akurat dalam memprediksi return saham. Menurut penelitian yang dilakukan olehSafitri et al, (2019) hasil perhitungan, metode Capital Asset Pricing Model lebih akurat dalam memprediksi return saham.Dalam penelitian ini, setelah menghitung Mean Absolute Deviation (MAD), Mean Squared Error (MSE), dan Mean Precentage Absolute Error (MAPE) dilakukan uji mann whitney u-test untuk mengetahui apakah ada perbedaan signifikan diantara kedua metode tersebut. Hasilnya Ha ditolak yang berarti bahwa tidak ada perbedaan signfikan antara metode CAPM dan APT hasil uji hipotesis mann whitney pada tabel MAD dan MSE tidak terdapat perbedaan keakuratan yang signfikan diantara kedua metode akan tetapi pada MAPE menyatakan bahwa kedua metode memiliki perbedaan keakuratan hal ini menunjukkan bahwa Ho diterima dan menolak Ha sehingga dapat disimpulkan bahwa dalam memprediksi return saham pada perusahaan consumer goods pada periode 2017 hingga 2020 tidak memiliki perbedaan yang akurat.Hal ini sesuai dengan penelitian yang dilakukan, Hasil penelitian Aqli, (2015) dalam memprediksi return saham tidak terdapat perbedaan akurasi diantara kedua model karena nilai Sig = 0.049 < 0.05.…”
unclassified
“…Iklim investasi berkembang pesat di Indonesia, banyak masyarakat tertarik untuk melakukan investasi, dan pasar modal merupakan tempat untuk berinvestasi yang lazim dan legal secara hukum. Penempatan sejumlah dana atau sumber daya lainnya bertujuan untuk mendapatkan keuntungan di masa datang disebut Investasi (Halim et al, 2000;Safitri et al, 2019;Tandelilin, 2010).…”
Section: Pendahuluanunclassified
“…Capital gain ataupun dividen merupakan bagian dari return saham. Return biasanya lebih diinginkan oleh investor dibandingkan risiko, yang artinya aktiva yang kurang berisiko lebih diminati investor namun sekaligus juga berharap mendapat return yang tinggi (Afzal & Pan, 2020;Evan et al, 2021;Jones, 2020;Safitri et al, 2019;Susanti et al, 2021).…”
Section: Pendahuluanunclassified